Historical dictionary of Costa Rica - Díaz Arias, David; Viales Hurtado, Ronny José; Marín Hernández, Juan José (Rowman & Littlefield, 2019)
"Historical Dictionary of Costa Rica contains a chronology, an introduction, appendixes, and an extensive bibliography. The dictionary section has over 1,000 cross-referenced entries on important personalities, politics, economy, foreign relations, religion, and culture."--Provided by publisher
Keywords: Costa Rica -- Encyclopedias.; Costa Rica -- History -- Dictionaries.; Costa Rica -- Bibliography.; HISTORY -- Latin America -- Mexico.; Costa Rica; encyclopedias.; dictionaries.; Bibliographies; Dictionaries; Encyclopedias; History; Encyclopedias.; Dictionaries.; Encyclopédies.; Dictionnaires.